Nonrandom RNAseq gene expression associated with RNAlater and flash freezing storage methods. (21st December 2018) - Passow, Courtney N.; Kono, Thomas J. Y.; Stahl, Bethany A.; Jaggard, James B.; Keene, Alex C.; McGaugh, Suzanne E.
Abstract: RNA sequencing is a popular next‐generation sequencing technique for assaying genome‐wide gene expression profiles. Nonetheless, it is susceptible to biases that are introduced by sample handling prior gene expression measurements. Two of the most common methods for preserving samples in both field‐based and laboratory conditions are submersion in RNAlater and flash freezing in liquid nitrogen. Flash freezing in liquid nitrogen can be impractical, particularly for field collections. RNAlater is a solution for stabilizing tissue for longer‐term storage as it rapidly permeates tissue to protect cellular RNA. In this study, we assessed genome‐wide expression patterns in 30‐day‐old fry collected from the same brood at the same time point that were flash‐frozen in liquid nitrogen and stored at −80°C or submerged and stored in RNAlater at room temperature, simulating conditions of fieldwork. We show that sample storage is a significant factor influencing observed differential gene expression. In particular, genes with elevated GC content exhibit higher observed expression levels in liquid nitrogen flash‐freezing relative to RNAlater storage. Further, genes with higher expression in RNAlater relative to liquid nitrogen experience disproportionate enrichment for functional categories, many of which are involved in RNA processing. This suggests that RNAlater may elicit a physiological response that has the potential to bias biological interpretations of expression studies. The biases introduced to observed gene expression arising from mimicking many field‐based studies are substantial and should not be ignored.